Pembangunan Obyek Wisata Berbasis Komunitas Lokal pada Jorong Kaluang Tapi, Nagari Koto Tangah, Kecamatan Tilatang Kamang, Kabupaten Agam - Lusi Andam Suri (Jurnal Sosiologi Andalas, 2019)
The development of Banto Royo tourism object, there is a social process in the form of cooperationbetween the local community of Jorong Kaluang. But with the initiator and sole investor, namely Ir. H. AndiSyahrandi. The objectives of this study are (1) To identify the process of developing Banto Royo tourism objects(2) to describe the forms of cooperation in the development of Banto Royo tourism objects. This study uses aqualitative approach with a descriptive type to understand the objectives. To understand this research, thetheory used is the social exchange from Peter M. Blau. The method used is a qualitative method and descriptiveresearch type. Data collection was carried out by in-depth interviews and observation and documentationcollection. Research informants were taken by purposive sampling (intentionally). The study found that duringthe Banto Royo planning process, local communities and investors held deliberations that resulted inagreements such as land loan agreements, profit sharing, and also the recruitment of workers. During theimplementation process, the construction of Banto Royo was carried out in cooperation with the localcommunity. In the monitoring and evaluation process, local people who become officers have various rules andregulations. The next result is a form of cooperation contained in the construction of Banto Royo such asmutual cooperation carried out by local communities and resulting in agreements, and cooperation with otherparties in various activities that reflect community-based tourism development.